Aspek Hukum dan Konstitusionalitas Kemenangan Kotak Kosong dalam Pilkada Serentak Tahun 2024 - Heri Suheri (Fakultas Hukum Universitas Bangka Belitung, 2025)
This research investigates the meaning, relevance, and consequences of the blank ballot win for the political, social, and cultural systems, as well as the media's role in molding public opinion. The study technique includes a literature review, case studies from various locations, and an evaluation of the legislation governing the legality of a single candidate. According to the findings, the blank ballot has become a symbol of popular protest against political competition and political parties' inadequate candidate selection systems. The success of the blank box can spur political system change, stimulate more rational political involvement, and put pressure on political parties to produce better competent candidates. However, this phenomena has the potential to produce short-term political instability in the form of election delays and leadership vacancies. Thus, the blank box serves as a democratic tool that protects residents' voting rights while simultaneously measuring the quality of local democracy.the democratic process. When there is just one eligible candidate pair, a blank